Green and Highly Efficient Wool Keratin Extraction by Microwave Induction Method - Du, Wenqian; Zhang, Liran; Zhang, Changhuan; Cao, Jianwei; Wang, Dongmin; Li, Hongwei; Li, Wenxia; Zeng, Jinling (Frontiers in Materials, 2022)
Keratin is a plentiful and renewable fibrous protein resource found in nature, but a great deal of keratin-containing waste causes environmental problems, especially wool waste, which accounts for the majority. Green and efficient extraction method of keratin based on microwave induction was studied. Compared with traditional thermal induction, the extraction time was shortened by half, and the dissolution rate of the wool was improved. The effects of the above two methods on the size, structure, crystallinity and thermal stability of wool keratin were studied by a series of analysis methods (e.g., attenuated total reflectance fourier transform infrared spectrometry (ATR-FTIR), Raman spectroscopy, X-ray diffraction spectroscopy (XRD), dynamic light scattering (DLS), thermogravimetric analysis (TGA) and so on). The results showed that under microwave irradiation, the disulfide bonds were destroyed greatly and the secondary structure changed significantly, which was beneficial to obtain wool keratin with lower crystallinity and smaller particle size.